2022
DOI: 10.1021/acs.inorgchem.2c00254
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopic Investigation and Electronic State Calculation for Ca2(Mn,Ti)O4 Black Pigments with High Near-Infrared (NIR) Reflectivity

Abstract: Layered perovskite A 2 BO4 compounds were studied by a combination of X-ray powder diffraction (XRD) analysis, Raman spectroscopy, and density functional theory (DFT) calculations. Ti4+-doped Ca2MnO4 ceramics with high near-infrared (NIR) reflectivity were selected as a test case. After elucidating their crystal structures (I41/acd) by XRD analysis, Raman spectroscopy was applied. Raman peaks were observed at approximately 178, 290, 330, 463, 500, and 562 cm–1, which were confirmed by DFT calculations, and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…The phonon frequencies of the Raman-active modes of Ca 2 MnO 4 were calculated by DFT using the refined crystal structure. The calculated and experimental Raman frequencies are listed in Table . For the phonon modes at the Γ-point for the I 4 1 / acd (No.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The phonon frequencies of the Raman-active modes of Ca 2 MnO 4 were calculated by DFT using the refined crystal structure. The calculated and experimental Raman frequencies are listed in Table . For the phonon modes at the Γ-point for the I 4 1 / acd (No.…”
Section: Resultsmentioning
confidence: 99%
“…The valence and conduction bands of Ca 2 MnO 4 are composed of O 2p and Mn 3d orbitals, respectively. 20 Consequently, Ca 2 (Mn,Ti)O 4 absorbed the visible light due to the interband transition between the O 2p and Mn 3d orbitals and reflected NIR light. Recently it was revealed that one of the factors leading to the enhanced NIR reflectivity by doping Ti 4+ was the reduced DOS near the Fermi level.…”
Section: Optical Properties and Xanesmentioning
confidence: 99%
See 3 more Smart Citations